Electroactive aniline tetramer–spider silks with conductive and electrochromic functionality. Issue 34 (10th August 2022) - Wan, Hung-Yu; Chen, Yi-Ting; Li, Guan-Ting; Wu, Hsuan-Chen; Huang, Tsao-Cheng; Yang, Ta-I.
Abstract : Spider silk composite fibers with high conductivity and mechanical strength were developed and their color could be controlled by different applied pH values and voltages. Abstract : Electroactive aniline tetramer–spider silk composite fibers with high conductivity and mechanical strength were developed using a dip coating method. The fabricated spider silk composite fibers retain the high mechanical strength (0.92 GPa) and unique reversible relaxation–contraction behavior of spider dragline silks. The aniline tetramer modified on the silk surface imparted electroactive properties to the composite fibers. The color of aniline tetramer/spider silk composite fibers could be controlled by applying different pH values and voltages. Furthermore, the composite fiber's resistivity could reach 186 Ω m which can conduct electrical current to light LEDs. This study could provide a valuable guideline for developing highly-conductive electrochromic spider silks for use in E-textiles.